Pengembangan Soal Berbasis HOTS (Higher Order Thinking Skills) pada Kurikulum 2013 - Naelatul Markhamah (Nusantara: Jurnal Pendidikan Indonesia, 2021)
Changes in the form of education assessment in Indonesia is currently one of them is the implementation of based assessment HOTS (Higher Order Thinking Skills). The purpose of applying based assessment HOTS is to equip the ability of learners in facing their future in the 21st century, which includes skills as learners are required to think critically, creatively, innovatively, communicatively and collaboratively. Therefore, the purpose of this research is to find out the development of HOTS-based questions in the 2013 curriculum which includes the understanding of HOTS, hots characteristics, and steps for drafting HOTS Problems as well as examples of HOTS problems. The method used in this study is qualitative research with documentation data collection technique. The results of this study show that HOTS characteristics or High-level thinking skills include critical, logical, reflective, metacognitive and creative. The characteristics of HOTS are measuring the ability to think at a high level, using contextual-based problems, diverse questions, not familiar or routine and descriptions. Then, in the preparation of the questions, there are several steps, namely analyzing the Basic Competencies that can be made into the question, compiling a grid of questions, choosing a contextual and interesting stimulus and writing a question item that corresponds to the question grid as well as making rubrics or key answers.